2010
DOI: 10.1016/j.jcat.2009.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of chloronitrobenzene to chloroaniline in supercritical carbon dioxide over Ni/TiO2: Significance of molecular interactions

Abstract: The hydrogenation of chloronitrobenzene to chloroaniline was investigated over Ni/TiO 2 at 35°C in supercritical CO 2 (scCO 2 ), ethanol, and n-hexane. The reaction rate followed the order of scCO 2 > n-hexane > ethanol. In scCO 2 , the selectivity to chloroaniline and to aniline over Ni/TiO 2 were 97-99.5% and <1%, respectively, in the conversion range of 9-100%. The high chemoselectivity to chloroaniline cannot be achieved over Ni/TiO 2 in ethanol and n-hexane. In situ high-pressure Fourier transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 46 publications
3
52
0
5
Order By: Relevance
“…However, these catalysts sometimes show low selectivity to anilines because of the formation of several poisonous reaction intermediates such as nitrosobenzenes, phenylhydroxyamines, azoxybenzenes, and azobenzenes whose formation and accumulation should be avoided for the green production of anilines. The present authors reported that, when the hydrogenation of nitrobenzene to aniline was carried out in/under pressurized CO 2 , the selectivity to aniline was much higher than that obtained in conventional organic solvents [21][22][23][24][25]. The higher selectivity is ascribed to interactions of CO 2 with the substrate and the intermediates.…”
Section: Introductionmentioning
confidence: 62%
“…However, these catalysts sometimes show low selectivity to anilines because of the formation of several poisonous reaction intermediates such as nitrosobenzenes, phenylhydroxyamines, azoxybenzenes, and azobenzenes whose formation and accumulation should be avoided for the green production of anilines. The present authors reported that, when the hydrogenation of nitrobenzene to aniline was carried out in/under pressurized CO 2 , the selectivity to aniline was much higher than that obtained in conventional organic solvents [21][22][23][24][25]. The higher selectivity is ascribed to interactions of CO 2 with the substrate and the intermediates.…”
Section: Introductionmentioning
confidence: 62%
“…[8][9][10] The cell was loaded with 2 cm 3 solvent, it was purged with CO2 three times, and then it was heated up to a temperature of 323 K while stirring. After the desired temperature was obtained, 4 MPa H2 was introduced, compressed CO2 was fed into the cell to the desired pressure, and then stirring was stopped after 2 min.…”
Section: Phase Behavior Observationmentioning
confidence: 99%
“…6 One of interesting actions of CO2 in CXLs is the interaction with functional groups of organic substrates and/or reaction intermediates, which would accelerate or retard the reaction rate and change the product distribution. The authors show the significance of molecular interactions of CO2 in the catalytic selective hydrogenation of -unsaturated aldehydes to saturated alcohols 7,8 and of nitro arenes to anilines 9,10 . In the latter, for example, 100% selectivity to anilines can be achieved at any conversion level up to 100% total conversion with supported nickel catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of these molecular interactions was demonstrated for several reactions in CXLs. One of noteworthy examples is selective hydrogenation of aromatic nitro compounds with a Ni/TiO 2 catalyst [9]. When a reaction mixture (H 2 , liquid substrate, solid catalyst) was pressurized by CO 2 , the total rate of conversion increased and the selectivity to the desired aniline products was almost 100% at any conversion level.…”
mentioning
confidence: 99%